El nuevo lujo y el Luxury Law: una mirada al presente y futuro - Fasson Llosa, Annalucía (2023)
The luxury law is a new specialization of law that consists of advising all companies that are dedicated, in their different categories, to the luxury economic sector. Likewise, in this article we will explain what the new luxury consists of and how the law is contributing to its development through the use of technology and sustainability.